New Stories from the Midwest 2012 - Brown, Jason Lee, 1973-; Latham, Shanie (Quarry Books, 2013)
This book presents a collection of stories that celebrate an American region too often ignored in discussions about distinctive regional literature. The editors solicited nominations from more than 300 magazines, literary journals, and small presses and narrowed the selection to 19 authors. The stories, written by Midwestern writers or focusing on the Midwest, demonstrate that the quality of fiction from and about the heart of the country rivals that of any other region. Guest editor John McNally introduces the anthology, which features short fiction by Charles Baxter, Dan Chaon, Christopher Mohar, Rebecca Makkai, Roxane Gay, Lee Martin, and others.